2020
DOI: 10.1111/jai.14100
|View full text |Cite
|
Sign up to set email alerts
|

Parasite acquisition by the invasive Chinese sleeper ( Perccottus glenii Dybowski, 1877) (Gobiiformes: Odontobutidae) in Latvia and Ukraine

Abstract: The Perccottus glenii is one of the most invasive of European fish species. During August-September 2019, we examined Chinese sleeper from six waterbodies in Latvia and Ukraine for parasites. Seventeen parasite species were registered, including two ciliate species, one coccidia, one monogenean, one cestode, six trematodes, three nematodes, one acanthocephalan, one parasitic copepod, and one bivalve glochidia. Maximum species richness was registered in Ukraine, with eight species at Vylkove and three species a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…As with Ponto-Caspian Gobiidae, and according to the interactions recorded in this review, it seems that the majority of native parasites acquired by P. glenii in its non-native range are larval stages, e.g., larvae of R. acus [35,74], S. contortus [35,40,166,169], Streptocara crassicauda (Creplin, 1829) [74], Triaenophorus crassus Forel, 1868 [74], Diplostomum chromatophorum (Brown, 1931) [35,171] and Opisthioglyphe ranae (Frölich, 1791) [35,40]. This observation could thus well be a general trend in non-native hosts/acquired parasites systems, complementary to the accepted idea that these systems include mainly generalist parasites.…”
Section: Acquisition Of Previously Introduced Parasitesmentioning
confidence: 70%
See 2 more Smart Citations
“…As with Ponto-Caspian Gobiidae, and according to the interactions recorded in this review, it seems that the majority of native parasites acquired by P. glenii in its non-native range are larval stages, e.g., larvae of R. acus [35,74], S. contortus [35,40,166,169], Streptocara crassicauda (Creplin, 1829) [74], Triaenophorus crassus Forel, 1868 [74], Diplostomum chromatophorum (Brown, 1931) [35,171] and Opisthioglyphe ranae (Frölich, 1791) [35,40]. This observation could thus well be a general trend in non-native hosts/acquired parasites systems, complementary to the accepted idea that these systems include mainly generalist parasites.…”
Section: Acquisition Of Previously Introduced Parasitesmentioning
confidence: 70%
“…Kvach et al [166] and attracted attention to the potential spillback that several species, namely the Acanthocephala Acanthocephalus anguillae (Müller, 1780) and A. lucii, the Nematoda Spiroxys contortus (Rudolphi, 1819) and P. tomentosa, the Cestoda Paradilepis scolecina (Rudolphi, 1819), Valipora campylancristrota (Wedl, 1855) and Ophiotaenia europaea Odening, 1963, the Monogenea Gyrodactylus luciopercae Gusev, 1962 and the Digenea Metorchis xanthosomus (Creplin, 1846) and Schiginella schigini (Bykhovskaja-Pavlovskaja, 1962), could undergo. Ophiotaenia europea, recorded from Germany, Ukraine and Russia, is of particular interest as it shows the possibility of establishing parasitological links between non-native fish and native reptiles, as it is transmitted to freshwater snakes Natrix tessellata (Laurenti, 1768) and Natrix natrix (Linnaeus, 1758) through fish consumption [35,[166][167][168][169]. This scenario does not only affect wild fauna, but can also have a notable impact on pets, e.g., M. xanthosomus was found several times in the introduced P. glenii [74,75,166,169] and in N. fluviatilis [133] and is of veterinary importance as it is known to infect dogs [170].…”
Section: Acquisition Of Previously Introduced Parasitesmentioning
confidence: 99%
See 1 more Smart Citation
“…While most of the parasite species found in Ukrainian pumpkinseed were represented predominantly by common native species acquired in their new range along the lower Danube basin (see Kulakovskaya and Koval, 1973;Kvach et al, 2020), most of these were only found accidentally, with low prevalence and abundance (Tab. 4), with just two native eye flukes, D. pseudospathaceum and T. clavate, found more commonly.…”
Section: Discussionmentioning
confidence: 99%
“…While Amur sleeper is efficient at utilizing various food resources ranging from ciliates to vertebrates, and can thus avoid competition with other species, there are also additional pathways through which it can affect the ecosystem: Amur sleeper can efficiently escape predation (Kati et al, 2015) making it more resilient than some of its competitors while at the same time it can transmit diseases to other species (Kvach et al, 2020; Pupins et al, 2023). As a generalist intermediate consumer, Amur sleeper can cause significant and hard‐to‐predict top‐down and bottom‐up effects in ecosystems it invades (Reshetnikov, 2013).…”
Section: Discussionmentioning
confidence: 99%